Steamship Service to Alaska (1897) - North American Transportation and Trading Company (1897)
Klondike: The commodious and fast sailing steamer Portland. Leaves Seattle Sept. 10 for Fort Get There, St. Michael's Island, Alaska, mouth of the Yukon River, making connections with the river steamers.Passengers will be landed at Circle City, Fort Cudahy and Klondike gold mines on or before June 15, 1898. Fare, including board, seven hundred dollars. Placer and quartz mines bought and sold. In the 1890s, the North American Transportation and Trading Company of Chicago, Illinois established stations and operated mines throughout Alaska and the Yukon Territory. Klondike Gold Rush Steamships, ferries and boats Transportation and communication Real estate and land development Cost and standard of living